The determinants of debt financing: The case of FinTech start-ups - Elisa Giaretta; Giusy Chesini (Journal of Innovation & Knowledge (JIK), 2021)
The purpose of this paper is to explore determinants of the debt financing of FinTech start-ups. Using a new hand-collected multisource database that maps FinTech start-ups incorporated in the UK from 2010 to 2015, this study examines how the characteristics of FinTech start-ups affect the types of financing used in the first three years after incorporation. The novelty of this study consists in the identification and analysis of the determinants that enable FinTech start-ups to obtain long-term debt and hence to finance their growth. The analysis is primarily conducted via a Tobit regression model. This paper contributes to the literature since we still have limited understanding of the financing of FinTech firms, even if academic literature examining the financing of start-ups has expanded in the last few years. The results from the empirical analysis demonstrate that unregulated FinTech start-ups are more likely to be financed with long-term debt. Asset structure, owner characteristics and the specific FinTech activity influence the funding source. Moreover, FinTech start-ups backed by equity investors receive less long-term debt funding than their peers. A better understanding of the debt financing of FinTech start-ups provides managers with valuable insights into ways of managing their firms. Furthermore, our results have relevant implications for the employment, competition and innovation, given the role that start-ups generally play in the economy. The study is limited to a sample of FinTech start-ups incorporated in an advanced economy, and thus the generalization of the presented results to developing economies will require caution.
Keywords: 650; Debt; Fintech; Regulation; Start-up; Tobit; Venture capital